2021
DOI: 10.1007/s00221-020-06005-4
|View full text |Cite
|
Sign up to set email alerts
|

Does exposure to startle impact voluntary reaching movements in individuals with severe-to-moderate stroke?

Abstract: When movements of individuals with stroke (iwS) are elicited by startling acoustic stimulus (SAS), reaching movements are faster, further, and directed away from the body. However, these startle-evoked movements also elicit task-inappropriate flexor activity, raising concerns that chronic exposure to startle might also induce heightened flexor activity during voluntarily elicited movement. The objective of this study is to evaluate the impact of startle exposure on voluntary movements during point-to-point rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Startle exposure resulted in faster and louder speech. These results were analogous to the finding that a startle during upper extremity movement produced a higher probability of muscle activity onset in severe poststroke subjects who were unable to activate their arm muscles on their own (38). Second, Ding-lan Tang examined movement variability during speech production perturbed by auditory feedback.…”
Section: Exploring Complex Motor Skills Beyond Unimanual Reachingsupporting
confidence: 65%
“…Startle exposure resulted in faster and louder speech. These results were analogous to the finding that a startle during upper extremity movement produced a higher probability of muscle activity onset in severe poststroke subjects who were unable to activate their arm muscles on their own (38). Second, Ding-lan Tang examined movement variability during speech production perturbed by auditory feedback.…”
Section: Exploring Complex Motor Skills Beyond Unimanual Reachingsupporting
confidence: 65%
“…At last, our research focused on the initiation of AMAs and did not include classic APA evaluation indicators, such as onset or velocity of displacement of body center of mass on the trunk ( 3 , 5 ) in this study. SE may affect the movement amplitude and velocity of the trunk and limbs of stroke survivors ( 30 , 31 ). The integration of a wearable inertial measurement unit with sEMG may better optimize our conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy subjects, the loud acoustic stimulus has been confirmed to increase the response frequency of AMAs during gait initiation ( 4 ). Moreover, some studies further revealed that the exposure to startling does not impact the upper-limb voluntary activities but enhances the actual reaching performance in stroke subjects ( 30 , 31 ). However, not all movement initiation can be triggered by SE early, it is negative in some distal finger manipulation activities ( 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 7 hemiplegic male volunteers post stroke (age: 61.57±12.03 (S.D) years; impaired side (L/R): 4/3, time since stroke: 7.63±6.51 (S.D) month) participated in the study. The inclusion criteria were moderate-to-severe upper extremity impairment (upper extremity Fugl-Meyer (UEFM) score <41/66 [28]) and sufficient cognitive/language abilities to follow instructions during the experiment (Mini-Mental Status Score >22). We excluded volunteers who had severe shoulder pain, relevant musculoskeletal injury, or fixed contraction deformity in the upper extremity.…”
Section: A Participantsmentioning
confidence: 99%